2020
DOI: 10.3390/polym12092102
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Hydrophobic Polyaniline/Silk Fibroin Electrochromic Nanofibers with Low Electrical Resistance

Abstract: Electronic textiles (E-textiles) have been an area of intense industrial and academic research for years due to their advanced applications. Thus, the goal of this study was to develop highly conductive silk fibroin electrochromic nanofibers for use in E-textiles. The silk nanofibers were prepared by an electrospinning technique, and the conductive polyaniline (PANI) was added to impart the electrical conductivity and electroactive property to the resultant electrospun silk composite nanofibers. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…According to Figure 5 , the water droplet took about 270 s to reach the angle 0° from 120°, which is in the range of hydrophobic surfaces. Even though the surface of PEICT ENM is hydrophobic [ 37 ], the cell infiltration observed was very good because of the interconnected nanofiber network with a smooth morphology, which also played an important role in cell adhesion. Additionally, the WCA test suggested that five minutes were enough as a resting period for fibroblast initial cell adherence on PEICT ENMs.…”
Section: Resultsmentioning
confidence: 99%
“…According to Figure 5 , the water droplet took about 270 s to reach the angle 0° from 120°, which is in the range of hydrophobic surfaces. Even though the surface of PEICT ENM is hydrophobic [ 37 ], the cell infiltration observed was very good because of the interconnected nanofiber network with a smooth morphology, which also played an important role in cell adhesion. Additionally, the WCA test suggested that five minutes were enough as a resting period for fibroblast initial cell adherence on PEICT ENMs.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, the strength and elongation at break of PMMA nanofibrous membrane is 0.59 MPa and 44.1%, respectively, although wrinkled PMMA fibers reported many times. In addition, the breaking strength of nanofiber membranes reported in the literature is generally lower than 6.79 MPa, such as silk fibroin 3.91 MPa 46 and 3.45 Mpa, 47 poly (lactic acid) 0.97 Mpa, 48 polycaprolactone 2.15 Mpa, 49 polyacrylonitrile 6.51, 50 4.3 51 and 3.8 52 MPa, polystyrene 1.5 Mpa, 53 PVDF 2.2 54 and 2.97 MPa 55 (Table 3). Moreover, the nanofiber membrane reported always showed poor elongation at break, almost lower than 50% (Table 3).…”
Section: Resultsmentioning
confidence: 97%
“…These electrochromic behaviors are similar to the related polyaniline studies reported in literature since the aniline tetramer is the smallest oligomer unit that can fully represent the structure of polyaniline. 40–44…”
Section: Resultsmentioning
confidence: 99%